Design and Construction of A 3-Dimensional Vibration Measurment Tool Using Accelerometer Sensors Based On The IoT For Implementations of Building Structures - Gabe, Totop; Yulkifli, Yulkifli; Yohandri, Yohandri; Ahadi, Suaidi (Department of Physics, Universitas Negeri Padang, 2024)
The building structure plays a crucial role in distributing the loads exerted by the building onto the ground, ensuring its strength to prevent collapse or damage. A common form of building damage is cracking due to vibrations. These vibrations can originate from both inside and outside the building, often at low frequencies. To address this, a vibration measuring instrument needs to be designed using a 3-Dimensional Accelerometer sensor to facilitate easier detection and data acquisition, thereby minimizing errors in measuring low vibrations caused by human activities that impact the durability of building structures. The research focuses on developing a tool to measure 3-dimensional vibrations in buildings using an Internet of Things (IoT)-based accelerometer sensor. This engineering research aims to design a 3-dimensional vibration measuring instrument. The resulting design includes performance specifications and system design specifications. The system's performance specifications cover the electronic circuit of the tool and the design of the measurement value monitoring display. The system employs the MPU6050 sensor to measure vibrations, with Arduino Uno as the main microcontroller and NodeMCU ESP32 for transmitting measurement data from Arduino to the web server. Experimental tests were conducted to measure vibration frequency by repeatedly dropping a 100-gram load from a height of 70 cm onto a wooden table. The load was dropped 10 times, maintaining a 2 cm distance from the coordinates of the measuring device. The experiments provided real-time measurement results, showing varying frequencies each second. The device successfully detected very low vibrations, with a minimum recorded frequency of 11.26 mHz and a peak of 93.18 mHz in the sixth experiment. The varying results across experiments were influenced by factors such as measurement sensitivity, filtering, sampling frequency, calibration, data processing, and noise minimization. The analysis confirmed that the tool could detect vibrations every second with high sensitivity, making it suitable for real-time detection of various low-frequency vibrations under consistent load conditions